Identifikasi Kesehatan Bibit Saninten (Castanopsis argentea Blume) di Persemaian Tonjong, Taman Hutan Raya Ir. H. Djuanda - Wahyuni, Dwi; Wilujeng, Sri; Lukmansyah, Lucky (Universitas Pattimura, 2025)
Tahura Djuanda's efforts to maintain the sustainability of Castanopsis argentea are by ensuring the success of its regeneration, which is kept in the Tonjong nursery. Therefore, Castanopsis argentea seedlings require routine seedling health monitoring to determine the percentage of seedlings in the healthy, unhealthy, and dead categories. This study aims to identify the health of Castanopsis argentea seedlings in the Tonjong nursery, Tahura Djuanda. Sampling uses random sampling, which randomly analyzes seedlings in 1 bed with 150 seedlings; health identification is carried out using the cumulative method of Forest Health Monitoring (FHM) and the Environmental Monitoring Assessment Program (EMAP). Castanopsis argentea seedlings in the Tonjong nursery, Tahura Djuanda, were identified as 51.33% unhealthy seedlings and the remaining 48.67% healthy seedlings. Unhealthy seedlings are caused mainly by pest attacks that attack the leaves and shoots of the seedlings. Another cause is pine needles that stick to the leaves of the seedlings. Proper handling is using insecticides and artificial parents or moving the bed's location to the shade of broad-leaf trees.